Pengembangan UMKM Melalui Penggunaan Media Informasi Teknologi - Andi Marwan Elhanafi; Imran Lubis; Tommy Tommy; Rosyidah Siregar; Liza Novietta; Ruswan Nurmadi (Jurnal Pengabdian Kepada Masyarakat Digital, 2022)
The benefits of Medium, Small and Micro Enterprises (MSMEs) carried out by the community are often only sufficient for the needs of daily life, have not yet reached the development stage. The community of MSME actors is faced with the problem of how-to-do-good promotion and marketing, thereby increasing consumers. Community Service Activities carried out by universities can provide a solution to this problem. Digital Promotion and Digital Marketing for MSME actors can be carried out through socialization and training. This of course is something that must be done so that MSME actors can adapt to the current digital era. This community service is carried out in Bukit Lawang Village. Business development is the target to be achieved for MSME actors.Keywords: Community Service, MSMEs, Digital Promotion, Digital Marketing, Business Development